Use of Numeric Rating Scale (NRS) as Visual Analogue Scale (VAS): Is this Clinically Significant? - lbrahim Farooq Pasha; Atiq Ur Rehman; Asim Niaz Naqvi; Syed Junaid Ismail; Salman Ashfaq; Muhammad Asad Qureshi (Pakistan Armed Forces Medical Journal, 2023)
Objective: To analyze statistically significant differences between the Numeric Rating Scale (NRS) and Visual Analogue Scale (VAS) in low back pain (LBP) patients.